Hockey Athlete’s Mood Level During Training in The Time of Covid-19 Pandemic - Yudi Hidayat; Sumbara Hambali (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2022)
The purpose of this research was to determine how big the level of mood and the factors that affect the mood of athletes during extracurricular hockey training, both independent training and joint training based on each indicator at SMAN 14 Tangerang Regency. This type of research is quantitative descriptive research with survey method. The population and sample in this study were all members of the hockey extracurricular at SMAN 14 Tangerang Regency, totaling 25 people and sampling using total sampling technique. The instrument used was a study a rating scale questionnaire in the form of a checklist. The number of question items in the questionnaire is 21 questions that have been tested for validity and reliability. The questionnaire about mood is divided into several indicators, including fatigue, angry mood, feeling ready, energetic and full of energy, tension, self-assessment, confused mood, depression. Data collection techniques were carried out online using the help of social media whatsapp and google form. Data calculation and analysis in this study through a quantitative approach in the form of percentages. Based on the results of the research, it showed that the mood level of hockey extracurricular members was in the low category, namely the self-assessment indicator (55,2%) while for the very low category the indicator of feeling ready (45,5%), the anger mood indicator (33,8%), confused mood indicator (31,7%), tension indicator and depression indicator (21,6%) and fatigue indicator (17,2%). Of all these indicators, self-assessment is in the low category and the fatigue indicator is in the very low category.